Conjugated Vinylgold(I)‐Vinylideneruthenium(II) Complexes and Related Organoruthenium Compounds: Stable Analogues of Intermediates Proposed in Dual Gold Catalysis. Issue 9 (27th April 2016) - Wieteck, Marcel; Larsen née Vilhelmsen, Mie Højer; Nösel, Pascal; Schulmeister, Jürgen; Rominger, Frank; Rudolph, Matthias; Pernpointner, Markus; Hashmi, A. Stephen K.
Abstract: The reaction of a platinum acetylide derived from a 1, 2‐dialkynylarene with a phosphanegold(I) species delivered a σ‐platinum‐π‐gold coordination to the same triple bond of the organic substrate. Cyclopentadienyl‐di(phosphanyl)ruthenium(II) acetylides of the same substrate type gave vinylgold(I)‐vinylideneruthenium(II) complexes in similar reactions. A switch to the corresponding cyclopentadienyl‐di(carbonyl)ruthenium(II) species with a phenyl group on the second alkyne provided vinylruthenium(II) complexes in which the ruthenium was still bound to the same carbon as in the starting material, with a tert ‐butyl group on the second alkyne vinylruthenium(II) complexes in which the ruthenium has migrated to another carbon, were obtained. This reactivity mimics the initial steps suggested for dual gold catalysis with these substrates and thus for the first time experimentally confirms the organometallic reactivity patterns proposed for the single steps. Abstract :